Estudios en Asteraceae de Colombia: primer registro del género Tragopogon L. (2016)
As result of recent explorations in the Andean Cordillera Oriental of Colombia, Tragopogon porrifolius L. (Asteraceae: Cichorieae) is reported for the first time for this country. This study provides ecological information, geographic distribution, photographs, and comments about the particular morphological characteristics of the new reported species.